2018
DOI: 10.1088/1361-648x/aacd84
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of two domain walls during spin-torque-induced coherent motion

Abstract: We show that the application of a spin-polarized current to a double p domain wall system with a variable distance between the walls results in an interaction between the two domain walls. The transmission spectrum changes from that of a spin-dependent resonant double barrier to one like a [Formula: see text] wall. In addition, the spin torque on each individual wall creates coupled motion in the domain walls. The walls move independently with a fast speed at large separations, but slow considerably at small s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that scattering from successive sharp DWs can induce non-aligned spin densities which lower the threshold for current induced DW motion and lead to ordering of the DWs. [34][35][36][37] This paper is organized as follows: In Sec. II we present the model and theory to find the STTs in magnetic DWs constrained in nano-contacts, which is used in Sec.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that scattering from successive sharp DWs can induce non-aligned spin densities which lower the threshold for current induced DW motion and lead to ordering of the DWs. [34][35][36][37] This paper is organized as follows: In Sec. II we present the model and theory to find the STTs in magnetic DWs constrained in nano-contacts, which is used in Sec.…”
Section: Introductionmentioning
confidence: 99%